Photographic light - Media West Home Video (Firm); Media West, Inc. (Santa Clara, CA : Media West Home Video, 1986)
Host Brian Ratty explains and illustrates many tips about the use of photographic light. He also covers principles of how light works and ideas and techniques to give better control and manipulate light
Light -- Exposure control -- Lighting
Keywords: Photography -- Lighting